2006
DOI: 10.1038/sj.npp.1301152
|View full text |Cite
|
Sign up to set email alerts
|

N-Desmethylclozapine, a Major Clozapine Metabolite, Acts as a Selective and Efficacious δ-Opioid Agonist at Recombinant and Native Receptors

Abstract: The present study examined the effects of N-desmethylclozapine (NDMC), a biologically active metabolite of the atypical antipsychotic clozapine, at cloned human opioid receptors stably expressed in Chinese hamster ovary (CHO) cells and at native opioid receptors present in NG108-15 cells and rat brain. In CHO cells expressing the d-opioid receptor (CHO/DOR), NDMC behaved as a full agonist both in stimulating [ 35 S]GTPgS binding (pEC 50 ¼ 7.24) and in inhibiting cyclic AMP formation (pEC 50 ¼ 6.40). NDMC inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
3
7
0
Order By: Relevance
“…Within the framework of the message-address model of opioid receptor pharmacology the binding pocket of the receptor can be divided into two regions: the lower, highly conserved, is involved in recognizing the message of the ligand (efficacy), the upper, poorly conserved among opioid subtypes, is responsible of discriminating the address (selectivity). A correspondence between Basin 1 and the upper region of the binding pocket and between Basin 2 and the lower part might account for the enhanced activity of DSM compared to CLZ [37], [38]. Interestingly, although DSM and CLZ sample very close spatial regions associated with Basin 1 (see Figure 4), the list of above-threshold interacting residues extracted from Figure 5 does not overlap, i.e., there are no residues that interact with both compounds in Basin 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the framework of the message-address model of opioid receptor pharmacology the binding pocket of the receptor can be divided into two regions: the lower, highly conserved, is involved in recognizing the message of the ligand (efficacy), the upper, poorly conserved among opioid subtypes, is responsible of discriminating the address (selectivity). A correspondence between Basin 1 and the upper region of the binding pocket and between Basin 2 and the lower part might account for the enhanced activity of DSM compared to CLZ [37], [38]. Interestingly, although DSM and CLZ sample very close spatial regions associated with Basin 1 (see Figure 4), the list of above-threshold interacting residues extracted from Figure 5 does not overlap, i.e., there are no residues that interact with both compounds in Basin 1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DSM activates -opioid receptors endogenously expressed in brain while in the brain membrane preparations CLZ displays negligible agonist activity [35], [37]. Determination of intrinsic efficacies by taking into consideration both the maximal [S]GTPS binding stimulation and the extent of receptor occupancy at which half-maximal effect occurred indicated that DSM has an efficacy value equal to 82% of that of the full -opioid-receptor agonist DPDPE, whereas CLZ displays much lower levels of agonist efficacy [37], [38]. Since the two compounds differ in a methyl group, they are particularly well suited for a comparative study, homing in on understanding the microscopic details of their interactions with the target.…”
Section: Introductionmentioning
confidence: 99%
“…CHO/DOR cells were developed by transfecting CHO-K1 cells with pcDNA3.1-Hygro(+)vector encoding the human d-opioid receptor (Onali and Olianas, 2007) using PolyFect (Qiagen GmbH, Hilden, Germany) as transfection reagent following the manufacturer's instructions. Cells were selected by their resistance to 1 mg·mL -1 of hygromycin for 4 weeks and cell clones were isolated by using cloning cylinders.…”
Section: Cell Culture and Transfectionsmentioning
confidence: 99%
“…This effect is antagonized by the non-selective opioid antagonist naloxone ( p < 0.05), implying an opioid mechanism of action is involved in clozapine-induced anti-nociception. Norclozapine has also been reported to act as a opioid receptor agonist (Onali and Olianas, 2007; Olianas et al, 2009). Activation of neural mu and kappa subtypes of opioid receptors have been reported to inhibit neurally mediated contraction of both circular and longitudinal muscle in the ileum of the guinea pig (Kosterlitz and Waterfield, 1972) and inhibit ileal peristalsis in vitro (Kromer et al, 1980) and opioids like morphine are potently constipating (Frantzides et al, 1992).…”
Section: Discussionmentioning
confidence: 99%